Advanced Clinical Usefulness of Ultrasonography for Diseases in Oral and Maxillofacial Regions. (27th April 2010) - Wakasugi-Sato, Nao; Kodama, Masaaki; Matsuo, Kou; Yamamoto, Noriaki; Oda, Masafumi; Ishikawa, Ayataka; Tanaka, Tatsurou; Seta, Yuji; Habu, Manabu; Kokuryo, Shinya; Ichimiya, Hisashi; Miyamoto, Ikuya; et al.
Abstract : Various kinds of diseases may be found in the oral and maxillofacial regions and various modalities may be applied for their diagnosis, including intra-oral radiography, panoramic radiography, ultrasonography, computed tomography, magnetic resonance imaging, and nuclear medicine methods such as positron emission tomography. Of these modalities, ultrasound imaging is easy to use for the detection of noninvasive and soft tissue-related diseases. Doppler ultrasound images taken in the B-mode can provide vascular information associated with the morphology of soft tissues. Thus, ultrasound imaging plays an important role in confirming the diagnosis of many kinds of diseases in such oral and maxillofacial regions as the tongue, lymph nodes, salivary glands, and masticatory muscles. In the present article, we introduce three new applications of ultrasonography: guided fine-needle aspiration, measurement of tongue cancer thickness, and diagnosis of metastasis to cervical lymph nodes.